The Camptandriidae of Iraq, with description of a new genus and notes on Leptochryseus Al-Khayat & Jones, 1996 (Crustacea: Decapoda: Brachyura) - Ng, Peter K. L.; Rahayu, Dwi Listyo; Naser, Murtada D. (Zootaxa, 2009)
Three species of camptandriid crabs (Crustacea: Brachyura: Ocypodoidea) are reported from Iraq: Tylodiplax indica Alcock, 1900, Manningis arabicum (Jones & Clayton, 1983) and Nasima dotilliformis (Alcock, 1900), all new records for the country. The taxonomy of the three species is treated in detail. Tylodiplax indica Alcock, 1900, is here referred to Opusia new genus, differing from Tylodiplax De Man, 1895, by numerous carapace and male gonopod characters. Manningis arabicum (Jones & Clayton, 1983) and Nasima dotilliformis (Alcock, 1900) are redescribed from the types or topotypic material, and more differences with allied genera recorded and discussed. An allied genus from Kuwait, Leptochryseus Al-Khayat & Jones, 1996, is shown to be a valid taxon. Nasima is shown to be very close to Leptochryseus, sharing important thoracic sternal, male abdominal and male first gonopod characters, differing only in carapace features and adults of Leptochryseus being sexually dimorphic in their chelipeds.